Iron Content of Some Popular Cooked Foods Consumed by the Rural School Children in Sri Lanka - D. Ruwani G. Perera; Dilantha Gunawardana; Renuka Jayatissa; A. Buddhika G. Silva (Journal of Food Quality)
Iron is an important micronutrient that can be found in different food sources in varying quantities. Iron deficiency is common in populations consuming cereal-based diets with little or no animal-derived food products. Rice is the staple for Sri Lankans, which may not provide sufficient bioavailable iron. Sri Lankan food composition table does not contain data on iron in home-cooked foods. Aim of the present study was to determine the iron content in commonly consumed home-cooked foods (rice, vegetables, green leaves, pulses, fish, etc.) by children aged 15-16 years. The study was carried out in eight schools at the Divisional Secretariat, Horana. The average iron values of cooked rice, vegetables, green leaves, pulses, and fish were 23.29 ± 14.46, 19.34 ± 9.90, 29.56 ± 13.64, 45.16 ± 22.28, and 46.72 ± 14.53 mg/kg, respectively. A serving of cooked red raw rice (rathu kekulu) provided the highest Estimated Daily Intake (EDI) of iron. The total EDI per serving for all categories was 6.39 ± 1.06 mg, contributing to the recommended daily allowance (RDA) of 42.62% of girls and 58.12% of boys as defined by the United States Department of Agriculture. Meanwhile, based on the Sri Lankan RDA, dietary iron contribution per serving ranges from 16.39% to 17.76% in girls and 16.39% to 21.31% in boys in the 15-16 years age category. Therefore, these home-cooked foods which were prepared using local recipes have high iron content and can replenish a major proportion of recommended quotidian values for iron intake.